Climate and forest properties explain wildfire impact on microbial community and nutrient mobilization in boreal soil - Eckdahl, Johan A.; Kristensen, Jeppe A.; Metcalfe, Daniel B. (Frontiers in Forests and Global Change, 2023)
The boreal landscape stores an estimated 40% of the earth's carbon (C) found in terrestrial vegetation and soils, with a large portion collected in thick organic soil layers. These ground stores are subject to substantial removals due to the centurial return of wildfire, which has strong impacts on the soil microbial community and nutrient cycling, which in turn can control ecosystem recovery patterns and process rates, such as C turnover. Currently, predictive knowledge used in assessing fire impacts is largely focused on ecosystems that experience only superficial burning and few robust observations exist regarding the effect that smoldering combustion in deeper active soil layers has on post-fire soil activity. This study provided a highly replicated and regionally extensive survey of wildfire impact on microbial community structure (using fatty acid biomarkers) and nutrient cycling (using in situ ionic resin capsules) across broad gradients of climate, forest properties and fire conditions within 50 separate burn scars and 50 additional matched unburnt boreal forest soils. The results suggest a strong metabolic shift in burnt soils due to heat impact on their structure and a decoupling from aboveground processes, releasing ecosystem N limitation and increasing mobilization of N, P, K, and S as excess in conjunction with an altered, C-starved microbial community structure and reduced root uptake due to vegetation mortality. An additional observed climatic control over burnt soil properties has implications for altered boreal forest function in future climate and fire regimes deserving of further attention.